Anti-freezing concrete prepared from nano material gamma-Al2O3 and preparation method of anti-freezing concrete

By using the combination of nanomaterials γ-Al2O3 and cement in the frozen-resistant concrete, the existing frozen-resistant concrete has poor durability and high cost, and has achieved efficient and economical freezing resistance improvement.

CN119822741APending Publication Date: 2025-04-15HEILONGJIANG ELECTRIC POWER SCIENCE RESEARCH INSTITUTE +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510077493.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing freezing concrete has poor freezing durability and high cost.

Method used

The nanomaterial γ-Al2O3 and cement are used to form a gelling material at a ratio of 99:1, and freezing concrete is prepared through specific ratios and dispersion processes.

Benefits of technology

It significantly improves the freezing durability and strength of concrete, reduces porosity and the number of harmful pores, improves density and freezing resistance, and has small dosage and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822741A_ABST
    Figure CN119822741A_ABST
Patent Text Reader

Abstract

The invention relates to anti-freezing concrete prepared from a nano material gamma-Al2O3 and a preparation method of the anti-freezing concrete, in particular to the anti-freezing concrete prepared from the nano material gamma-Al2O3 and the preparation method of the anti-freezing concrete. The invention aims to solve the problems of poor anti-freezing durability and high manufacturing cost of the existing anti-freezing concrete. The concrete disclosed by the invention is prepared from a cementing material (cement and a nano material gamma-Al2O3), coarse aggregate, fine aggregate, a high-efficiency water reducing agent, a flocculating agent and water. The preparation method comprises the following steps: adding the high-efficiency water reducing agent into water according to the raw material ratio, stirring, adding the nano material gamma-Al2O3, dispersing by using an ultrasonic dispersion instrument, adding into the mixed aggregate and cementing material, and uniformly stirring to prepare the concrete. The concrete disclosed by the invention has the characteristics of simple preparation process, small number of harmful holes, high strength, good frost resistance and the like. The preparation method is applied to the field of preparation of anti-freezing concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to frost-resistant concrete prepared by utilizing nano material γ-Al2O3 and a method thereof. Background Art

[0002] Cement concrete is the most widely used and largest amount of civil engineering material. It is cheap, easy to construct and has excellent performance. Cement concrete uses cement paste as a binder to bind aggregates (such as fine sand, graded crushed stone, etc.) together and harden to form cement stone with certain mechanical properties. Cement concrete is widely used in the construction of houses, roads, bridges, dams and other projects in my country. When these projects are constructed in special environments, the performance of concrete will be seriously affected, especially the durability will be affected by chloride ion corrosion, sulfate erosion, freeze-thaw damage, etc. For example, in severe cold environments, concrete structures will be affected by the frost heave of water molecules and produce freeze-thaw damage. The attenuation of concrete durability not only shortens the service life of concrete structures but also greatly increases maintenance costs.

[0003] In severe cold regions, freeze-thaw damage is one of the main manifestations of concrete building diseases. Freeze-thaw damage will have a serious impact on the normal operation and service life of the building, and its maintenance cost is high, so it is imperative to improve the frost resistance and durability of concrete. Research on improving the frost resistance of concrete mainly focuses on the addition of air-entraining agents, fibers and nanomaterials. The addition of air-entraining agents to concrete can effectively improve the pore structure and reduce the occurrence of frost damage, but it will have an adverse effect on the strength performance of concrete. Therefore, in cold regions, the addition of air-entraining agents is generally not used to improve the frost resistance and durability of concrete. Fibers can improve the tensile strength of concrete, thereby improving its frost resistance and durability. This is mainly due to the bridging effect of fibers, that is, fibers connect different components inside the concrete to form an overall skeleton structure, but the degree of improvement of fibers on the frost resistance and durability of concrete is very limited. It is known that nanomaterials can improve the microstructure of concrete and improve the physical and mechanical properties of concrete due to their unique physical and chemical properties, but there are different opinions on whether they can improve the frost resistance and durability of concrete. At present, the nanomaterials for improving the frost resistance and durability of concrete are mainly concentrated on silica, which is mainly achieved by reducing the harmful porosity and refining microcracks in concrete through filling, nucleation and volcanic ash effects. However, there are many shortcomings in the preparation of nano-silica frost-resistant concrete. First, the specific surface area of ​​silica with the same nano-scale particle size is large, and it is easy to agglomerate in aqueous solution, making it difficult to prepare a homogeneous suspension, resulting in a serious decrease in the filling, nucleation and volcanic ash effects of nanomaterials; secondly, to improve the frost resistance of concrete with the same efficiency, the amount of nano-silica added is much larger than that of alumina, resulting in higher construction costs and greater dispersion costs. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of poor frost resistance and high construction cost of existing frost-resistant concrete, and to provide an frost-resistant concrete prepared by using nano material γ-Al2O3 and a method thereof.

[0005] The invention discloses an antifreeze concrete prepared by using nano material γ-Al2O3, which comprises 100 parts of cementitious material, 226-276 parts of coarse aggregate, 139-169 parts of fine aggregate, 0.5-1.5 parts of high-efficiency water reducing agent and 35-45 parts of water in parts by mass; wherein the cementitious material comprises cement and the nano material γ-Al2O3 in a mass ratio of 99:1.

[0006] A method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 is carried out in the following steps:

[0007] 1. Weigh the raw materials according to the proportion of 100 parts by mass of cementitious material, 226-276 parts by mass of coarse aggregate, 139-169 parts by mass of fine aggregate, 0.5-1.5 parts by mass of high-efficiency water reducing agent and 35-45 parts by mass of water; wherein the cementitious material is composed of cement and nano material γ-Al2O3 in a mass ratio of 99:1;

[0008] 2. Add the high-efficiency water reducer into water and stir for 3-5 minutes, add the nano material γ-Al2O3, and disperse it with an ultrasonic disperser to obtain a suspension;

[0009] 3. Mix the cement, fine aggregate and coarse aggregate and stir, then pour in the suspension and stir until it is evenly mixed to obtain frost-resistant concrete.

[0010] The nano-alumina modified concrete of the present invention can overcome the influence of low-temperature curing on its performance. Its strength under low-temperature curing is higher than that of unmodified concrete under standard curing, thereby promoting the construction of concrete in cold areas and further improving the frost resistance and durability of concrete (the frost resistance strength is significantly higher than that of nano-silicon dioxide modified concrete). The present invention can effectively solve all the above problems and fully play the positive effects of small dosage, low cost, high efficiency and easy dispersion. The concrete of the present invention has the characteristics of simple preparation process, small number of harmful pores, high strength and good frost resistance. The dosage of nano-material γ-Al2O3 in concrete is ≤3%, which realizes the high-value utilization of ordinary silicate cement and reduces carbon emissions. The nano-material γ-Al2O3 can improve the frost resistance and durability of concrete mainly because of its filling, nucleus and volcanic ash effects, which reduce the internal porosity of concrete, greatly reduce harmful pores, and greatly improve density, thereby hindering the penetration of water into the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is the nano-alumina suspension dispersed in Example 1. DETAILED DESCRIPTION

[0012] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0013] Specific implementation method 1: In this implementation method, an antifreeze concrete prepared using nano material γ-Al2O3 is composed of 100 parts of cementitious material, 226-276 parts of coarse aggregate, 139-169 parts of fine aggregate, 0.5-1.5 parts of high-efficiency water reducing agent and 35-45 parts of water in mass parts; wherein the cementitious material is composed of cement and nano material γ-Al2O3 powder in a mass ratio of 99:1.

[0014] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the cement is PO 42.5 ordinary Portland cement. Other aspects are the same as the specific implementation method 1.

[0015] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the coarse aggregate is diabase continuously graded crushed stone with a particle size of 5 to 20 mm. Other aspects are the same as specific implementation method 1 or 2.

[0016] Specific implementation method 4: This implementation method is different from the specific implementation methods 1 to 3 in that the fine aggregate is natural river sand with a particle size of less than 4.75 mm. Other aspects are the same as the specific implementation methods 1 to 3.

[0017] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the high-efficiency water reducing agent is a polycarboxylic acid water reducing agent with a water reducing efficiency of 25%. Other aspects are the same as those of specific implementation methods 1 to 4.

[0018] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the particle size of the γ-Al2O3 powder is 5 to 20 nm. The rest is the same as specific embodiments 1 to 5.

[0019] Specific implementation method seven: In this implementation method, a method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 is carried out in the following steps:

[0020] 1. Weigh the raw materials according to the proportion of 100 parts by mass of cementitious material, 226-276 parts by mass of coarse aggregate, 139-169 parts by mass of fine aggregate, 0.5-1.5 parts by mass of high-efficiency water reducing agent and 35-45 parts by mass of water; wherein the cementitious material is composed of cement and nano material γ-Al2O3 in a mass ratio of 99:1;

[0021] 2. Add the high-efficiency water reducer into water and stir for 3 to 5 minutes, add the nano material γ-Al2O3, and disperse it with an ultrasonic disperser to obtain a suspension;

[0022] 3. Mix the cement, fine aggregate and coarse aggregate and stir, then pour in the suspension and stir until it is evenly mixed to obtain frost-resistant concrete.

[0023] Specific embodiment 8: This embodiment differs from specific embodiment 7 in that: in step 2, stirring is performed at a rotation speed of 800 to 1200 rpm. The rest is the same as specific embodiment 7.

[0024] Specific embodiment 9: This embodiment is different from specific embodiment 7 or 8 in that: Step 2 is dispersed by ultrasonic dispersion instrument for 30 minutes. The rest is the same as specific embodiment 7 or 8.

[0025] Specific embodiment 10: This embodiment differs from specific embodiments 7 to 9 in that: Step 3: Pour cement, fine aggregate and coarse aggregate into a mixer and stir for 1 to 2 minutes. The rest is the same as specific embodiments 7 to 9.

[0026] The following examples are used to verify the beneficial effects of the present invention:

[0027] Example 1

[0028] A method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 is carried out in the following steps:

[0029] 1. Weigh raw materials according to the proportion of 100 parts of cementitious material, 226-276 parts of coarse aggregate, 136-169 parts of fine aggregate, 0.5-1.5 parts of high-efficiency water reducer and 35-45 parts of water by mass; wherein the cementitious material is composed of cement and nano material γ-Al2O3 in a mass ratio of 99:1; the coarse aggregate is diabase continuous graded crushed stone with a particle size of 5-20mm; the fine aggregate is natural river sand with a particle size of less than 4.75mm; the high-efficiency water reducer is a polycarboxylic acid water reducer with a water reduction efficiency of 25%.

[0030] 2. Add the high-efficiency water reducer into water, stir at a speed of 800-1200 rpm for 3-5 min, then add the nano material γ-Al2O3, and disperse it with an ultrasonic disperser to obtain a suspension;

[0031] 3. Pour cement, fine aggregate and coarse aggregate into a mixer and stir for 1 to 2 minutes, then pour in the suspension and stir until it is evenly mixed to obtain the prepared concrete.

[0032] The cement in this embodiment is PO 42.5 ordinary Portland cement, and the chemical composition is shown in Table 1; the nanomaterial γ-Al2O3 powder, and the physical properties are shown in Table 2. The nanoparticles of the nanomaterial γ-Al2O3 are tiny, and the molecular forces between the particles make it easy to agglomerate into blocks, and it is not easy to disperse evenly in the solution. Ultrasonic waves have high energy and strong directionality, and can propagate quickly in the solution, causing the solution to flow to form a cavitation field and quickly generate closed microbubbles. The energy released during the bubble closure process weakens the molecular forces between the particles, allowing the particles to be evenly dispersed in the solution. A uniform nano-alumina solution can be obtained by ultrasonic dispersion, Figure 1 Dispersed nano-alumina suspension. The specific dispersion process is as follows: first, pour the polycarboxylic acid high-efficiency water reducer with an alkali water efficiency of 25% into the water, stir it at a speed of 800-1200 rpm for 3-5 minutes to dissolve it, then add nano-alumina into the solution, and then disperse it with an ultrasonic disperser for 30 minutes to finally obtain a uniformly dispersed suspension. The aggregates used in the antifreeze concrete are natural river sand with a particle size of less than 4.75mm and diabase crushed stone with a continuous grade of 5-20mm. The specific mix ratio of the concrete is shown in Table 3.

[0033] Table 1 Chemical composition of cement

[0034]

[0035] Table 2 Physical properties of nanomaterial γ-Al2O3

[0036]

[0037] Table 3 Antifreeze concrete mix ratio (unit: kg / m 3 )

[0038]

[0039] Ordinary concrete and nano-silica modified concrete were used for comparison, wherein the preparation method of the nano-silica modified concrete is as follows: adding a high-efficiency water reducer into water, stirring at a speed of 800 to 1200 rpm for 3 to 5 minutes, then adding nano-silica, dispersing with an ultrasonic disperser to obtain a suspension; pouring cement, fine aggregate, and coarse aggregate into a mixer and stirring for 1 to 2 minutes, then pouring the suspension into the mixer and stirring until the mixture is uniformly stirred to obtain the nano-silica modified concrete.

[0040] The performance improvement of frost-resistant concrete compared with ordinary concrete and nano-silica modified concrete is shown in Table 4 and Table 5:

[0041] Table 4 Improvement of frost-resistant concrete performance compared to ordinary concrete

[0042]

[0043] Table 5 Performance improvement of frost-resistant concrete relative to nano-silica modified concrete

[0044]

[0045] It can be seen from Tables 4 and 5 that the performance of frost-resistant concrete has been greatly improved. It not only improves the compressive strength under standard curing, but also improves the compressive strength under low temperature (-5 to 5°C) curing; its porosity under standard and negative temperature curing is greatly reduced, and the cement stone is more homogeneous and dense; through 300 rapid freeze-thaw tests, it is found that its mass loss rate, dynamic elastic modulus attenuation rate and compressive strength reduction rate are all greatly reduced, indicating that it has strong frost resistance and durability.

Claims

1. A frost-resistant concrete prepared using nanomaterial γ-Al2O3, characterized in that The frost-resistant concrete is composed of 100 parts of cementitious materials, 226-276 parts of coarse aggregates, 139-169 parts of fine aggregates, 0.5-1.5 parts of high-efficiency water reducing agents and 35-45 parts of water in terms of mass proportions; wherein the cementitious materials are composed of cement and nano material γ-Al2O3 powder in a mass ratio of 99:

1.

2. The frost-resistant concrete prepared by using the nano material γ-Al2O3 according to claim 1, characterized in that The cement is PO 42.5 ordinary Portland cement.

3. The frost-resistant concrete prepared by using the nano material γ-Al2O3 according to claim 1, characterized in that The coarse aggregate is diabase continuously graded crushed stone with a particle size of 5 to 20 mm.

4. The frost-resistant concrete prepared by using the nano material γ-Al2O3 according to claim 1, characterized in that The fine aggregate is natural river sand with a particle size less than 4.75 mm.

5. The frost-resistant concrete prepared by using the nano material γ-Al2O3 according to claim 1, characterized in that The high-efficiency water reducer is a polycarboxylic acid water reducer with a water reduction efficiency of 25%.

6. The frost-resistant concrete prepared by using the nano material γ-Al2O3 according to claim 1, characterized in that The particle size of the γ-Al2O3 powder is 5 to 20 nm.

7. A method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 as claimed in claim 1, characterized in that The preparation method is carried out according to the following steps:

1. Weigh the raw materials according to the proportion of 100 parts by mass of cementitious material, 226-276 parts by mass of coarse aggregate, 139-169 parts by mass of fine aggregate, 0.5-1.5 parts by mass of high-efficiency water reducing agent and 35-45 parts by mass of water; wherein the cementitious material is composed of cement and nano material γ-Al2O3 in a mass ratio of 99:1; 2. Add the high-efficiency water reducer into water and stir for 3-5 minutes, add the nano material γ-Al2O3, and disperse it with an ultrasonic disperser to obtain a suspension; 3. Mix the cement, fine aggregate and coarse aggregate and stir, then pour in the suspension and stir until it is evenly mixed to obtain frost-resistant concrete.

8. The method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 according to claim 7, characterized in that In step 2, stirring is performed at a rotation speed of 800 to 1200 rpm.

9. The method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 according to claim 7, characterized in that Step 2: Disperse in ultrasonic disperser for 30 minutes.

10. The method for preparing frost-resistant concrete using nanomaterial γ-Al2O3 according to claim 7, characterized in that Step 3: Pour cement, fine aggregate and coarse aggregate into a mixer and mix for 1 to 2 minutes.

Citation Information

Cited By

  • Construction application and production method of high-flowability super-early-strength concrete at-15 DEG C

    CN121292878A